PERSEPSI PEDAGANG ATAS PENOLAKAN UANG LOGAM SEBAGAI ALAT TUKAR DI KABUPATEN SIMEULUE (STUDI DI PAJAK INPRES KABUPATEN SIMEULUE) - Teguh Putra Lahanta, Zulfadhli, Ismail (Jurnal Economica Didactica, 2019)
ABSTRACTThis study is entitled The traders perception of rejecting coins as a tool exchange in Simeulue Regency (A study in pajak inpres in Simeulue Regency). The purpose of this research is to know how the traders perception of rejecting coins as a tool exchange in Simeulue Regency. In this research, the approach employed a qualitative approach with the researchs type of descriptive. The research location was conducted at pajak inpres in Simeulue Regency which is the largest and completest traditional market in Simeulue Regency. The respondents in this research are 15 persons consisted of 10 traders and 5 additional people. The data collection in this research was obtained from an interview. The data collection was obtained by doing field research at pajak inpres in Simeulue Regency. Moreover, people did not use coins as a tool exchange anymore. However, they do not agree with the coins rejection as a tool exchange in Simeulue Regency. The reasons for coins rejection were caused by the high price of goods in Simeulue Regency and the information about coins rejection as a tool exchange increase in the public. Furthermore, other reasons are the poor service by the bank and the minimum existence of banks in Simeulue Regency. People and traders rejected coins because other traders and people also rejected coins as a tool exchange. Also, the coins rejection as a tool exchange has no effects on the trading activity. Furthermore, they do not know of the criminal offense for people who reject or not accept the coins. During the coins rejection as a tool exchange, there is no serious policy from the government or other related institutions to overcome it. It can be concluded that the coins rejection as a tool exchange in Simeulue Regency was not approved by all respondents, but it would always happen if one of the traders or some people still reject the coins. Therefore, people should increase their awareness to reaccept the coins as a tool exchange in Simeulue Regency by the firmness of law to make them aware to reaccept the coins as a tool exchange.Key Words: Coins Rejection